Comparative Studies And Forested Areas On Biodiversity And Land-Use Change (LUC) In Penang Island - Masum, Kazi Mohammad (2017)
The Global Forest Resources Assessment 2015 reported an increasing rate of privately owned forests on a global scale. However, deforestation was found to be very active in privately owned hill forest areas of Malaysia. Penang State was purposively chosen as it has been experiencing rapid and radical changes due to urban expansion over the last three decades. In this study, effect of differential management on land-use changes (LUC) and biodiversity were analysed. Analyses of land-use changes (LUC) were done by PCI Geomatica using Landsat images from 1991 to 2015 and future trends of LUC were assessed using EXCEL forecast function.